Implementasi Decision tree Untuk Prediksi Kanker Paru-Paru - Faurika, F; Khudori, Ahsanun Naseh; Haris, M Syauqi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Lung cancer is a disorder of the lungs due to changes in respiratory tract epithelial cells which cause uncontrolled cell division and growth. Lung cancer is caused by several factors such as radiation exposure, smoking, heredity, gender, air pollution, and unhealthy lifestyles. Lung cancer can be detected when the cancer has entered an advanced stage. The large amount of lung cancer diagnosis data currently available can be used to predict lung cancer based on patterns in the data. One of the results of technological advances that can learn patterns in data is machine learning, which has currently made many positive contributions in the health sector. This research aims to predict lung cancer using a decision tree algorithm. This research produces rules based on decision trees which are built and then evaluated to produce the same accuracy, precision, recall, and F1-Score of 100%.